2002
DOI: 10.1212/wnl.59.7.998
|View full text |Cite
|
Sign up to set email alerts
|

MRI predictors of early conversion to clinically definite MS in the CHAMPS placebo group

Abstract: For patients with positive MRI at the time of their initial neurologic event, both gadolinium-enhancing lesions and the Barkhof criteria are predictors for development of CDMS over a short interval. However, these results, based on a combined CDMS/MRI outcome, suggest that the majority of these patients are already in the earliest stages of MS, regardless of whether any further MRI criteria are met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…14 In those who demonstrated two or more Gdenhancing lesions at baseline, 52% developed CDMS by 18 months and 84% had either developed CDMS or exhibited temporal dissemination of disease activity on MRI after 18 months. 43 By contrast, in patients with fewer than two enhancing lesions at baseline, only 24% developed CDMS at 18 months (class I evidence). In this study, 60% of the placebo patients not meeting MRI (a) criteria (see table 3) went on to develop temporal dissemination of disease activity by either experiencing another exacerbation or developing new MRI lesions.…”
Section: Relationship Of Baseline Gd Enhancement and Subsequent Mri Fmentioning
confidence: 99%
“…14 In those who demonstrated two or more Gdenhancing lesions at baseline, 52% developed CDMS by 18 months and 84% had either developed CDMS or exhibited temporal dissemination of disease activity on MRI after 18 months. 43 By contrast, in patients with fewer than two enhancing lesions at baseline, only 24% developed CDMS at 18 months (class I evidence). In this study, 60% of the placebo patients not meeting MRI (a) criteria (see table 3) went on to develop temporal dissemination of disease activity by either experiencing another exacerbation or developing new MRI lesions.…”
Section: Relationship Of Baseline Gd Enhancement and Subsequent Mri Fmentioning
confidence: 99%
“…Patients experiencing a CIS with rapid complete recovery, a low T2 lesion burden (<3 lesions), no evidence of brain atrophy, and an older age at CIS onset (>38 years) may elect to monitor their condition before initiation of therapy, with the knowledge that there are no truly low-risk groups identified with any certainty by these clinical and MRI criteria. 18 Overall, it is reassuring that all three intervention trials reviewed here consistently demonstrate the benefits of early use of IFNβ in delaying conversion to CDMS. However, in the absence of head-to-head studies in this population, and because the IFNβ formulations cannot be readily differentiated based on their clinical or neurologic efficacies in the ETOMS, CHAMPS, and BEN-EFIT studies, the choice of treatment may be based on efficacy of IFNβ, particularly over the short term.…”
Section: Champsmentioning
confidence: 59%
“…This effect remained after controlling for baseline MRI characteristics and syndrome type. 18 Several natural history studies have suggested that optic neuritis at CIS onset may signify a form of MS with a better prognosis compared with other syndromes. [24][25][26] However, among patients with abnormal cranial MRI studies and monosymptomatic presentation at CIS onset, syndrome type appears to have little effect on disease course.…”
Section: Results From Phase 3 Studies Of Ifnβ In Patients With a Cismentioning
confidence: 99%
See 2 more Smart Citations